Assessment of the sublingual microcirculation with the GlycoCheck system: Reproducibility and examination conditions - Eickhoff, Mie Klessen; Winther, Signe Abitz; Hansen, Tine Willum; Diaz, Lars Jorge; Persson, Frederik; Rossing, Peter; Frimodt-Møller, Marie (PloS one, 2020)
The glycocalyx is an extracellular layer lining the lumen of the vascular endothelium, protecting the endothelium from shear stress and atherosclerosis and contributes to coagulation, immune response and microvascular perfusion. The GlycoCheck system estimates glycocalyx' thickness in vessels under the tongue from perfused boundary region (PBR) and microvascular perfusion (red blood cell (RBC) filling) via a camera and dedicated software. Evaluating reproducibility and influence of examination conditions on measurements with the GlycoCheck system. Open, randomised, controlled study including 42 healthy smokers investigating day-to-day, side-of-tongue, inter-investigator variance, intraclass-correlation (ICC) and influence of examination conditions at intervals from 0-180 minutes on PBR and RBC filling. Mean (SD) age was 24.9 (6.1) years, 52% were male. There was no significant intra- or inter-investigator variation for PBR or RBC filling nor for PBR for side-of-tongue. A small day-to-day variance was found for PBR (0.012μm, p = 0.007) and RBC filling (0.003%, p = 0.005) and side-of-tongue, RBC filling (0.025%, p = 0.009). ICC was modest but highly improved by increasing measurements. Small significant influence of cigarette smoking (from 40-180 minutes), high calorie meal intake and coffee consumption was found. The latter two peaking immediately and tapering off but remained significant up to 180 minutes, highest PBR changes for the three being 0.042μm (p<0.05), 0.183μm (p<0.001) and 0.160μm (p<0.05) respectively. Measurements with the GlycoCheck system have a moderate reproducibility, but highly increases with multiple measurements and a small day-to-day variability. Smoking, meal and coffee intake had effects up to 180 minutes, abstinence is recommended at least 180 minutes before GlycoCheck measurements. Future studies should standardise conditions during measurements.